The intellectual information systems and their using in economy and education (Journal of Information Technologies in Education (ITE), 2007)
In this article the subject is about using of intellectual informative models in economy and education. In modern terms at the level of large industrial enterprises the in-plants informative expert systems orientated on concrete researches analytical tasks are popular. Those informative systems which are taught and able automatically to form knowledge bases for classification of problems regions of prognostication are perspective.